PENGARUH INSIDER OWNERSHIP, KEBIJAKAN HUTANG DAN FREE CASH FLOW TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN - BUDI MARDASARI, RIZKY (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract : The purpose of this study was to determine the effect of insider ownership, debt policy and free cash flow are registered in the manufacturing sector in the period 2006-2012. The population used in this study are all publicly traded companies listed on the Indonesia Stock Exchange. This study used purposive sampling method, with a population of 141 companies and a sample of 8 companies. This study uses path analysis with SPSS version 20.00. The analysis technique used in this study is a classic assumption test, t-test statistics for testing the partial regression coefficients and sobel test. The results showed that the debt policy has a positive effect on firm value. Free cash flow has a negative effect on firm value. Insider ownership has a positive effect on dividend policy.Dividend policy is influential in mediating the relationship between the debt policies to the firm value. Keyword:firm value, dividend policy, insider ownership, debt policy, and free cash flow.